Optimising islanded AC microgrid control: A hierarchical approach with FCS-VMPC and consensus algorithm - Khan, Zawar; Muhammad Aamir, Muhammad Aamir; Khan, Rizwanullah; Mohd Yousof, Mohd Fairouz (elsevier, 2025)
The growing integration of distributed generation (DG) from renewable energy sources (RES) in modern power systems highlights the need for advanced hierarchical control strategies. The primary layer is typically implemented using a linear controller, while the secondary control relies on complex control strategies. Due to this hierarchical control AC microgrid (MG) faces unequal power sharing or power quality problems. This paper presents a hierarchical control scheme for islanded AC MG to effectively manage power between DG units. The scheme operates with a non-linear controller consisting of finite control set-voltage model predictive control (FCS-VMPC) at the primary layer and a consensus algorithm at the secondary layer. Primary control, utilizing droop control and FCS-VMPC, is independently implemented for frequency and voltage regulation across DG units. Droop control manages power distribution between DG units and loads. Meanwhile, the secondary layer based on the consensus algorithm collaborates with FCS-VMPC to establish reference voltage values and adjust deviations at the primary level. The proposed hierarchical control facilitates communication between adjacent nodes by a sparse network. This reduces the complexity of the network with FCS-VMPC at the primary and consensus algorithm at the secondary layer. The secondary controller’s effectiveness is tested against transients, unbalanced loads, and dynamic load changes. The results confirm that the MG effectively supplies power while maintaining stable voltage and frequency, achieving a total harmonic distortion (THD) of 0.95 % and a maximum voltage deviation of 0.0001 pu respectively.